To TQIP or Not to TQIP? that is the Question. Issue 4 (April 2014) - Heaney, Jiselle Bock; Guidry, Chrissy; Simms, Eric; Turney, Jennifer; Meade, Peter; Hunt, John P.; McSwain, Norman E.; Duchesne, Juan C.
The Trauma Quality Improvement Program (TQIP) reports a feasible mortality prediction model. We hypothesize that our institutional characteristics differ from TQIP aggregate data, questioning its applicability. We conducted a 2-year (2008 to 2009) retrospective analysis of all trauma activations at a Level 1 trauma center. Data were analyzed using TQIP methodology (three groups: blunt single system, blunt multisystem, and penetrating) to develop a mortality prediction model using multiple logistic regression. These data were compared with TQIP data. Four hundred fifty-seven patients met TQIP inclusion criteria. Penetrating and blunt trauma differed significantly at our institution versus TQIP aggregates (61.9 vs 7.8%; 38.0 vs 92.2%, P < 0.01). There were more firearm mechanisms of injury and less falls compared with TQIP aggregates (28.9 vs 4.2%; 8.5 vs 34.8%, P < 0.01). All other mechanisms were not significantly different. Variables significant in the TQIP model but not found to be predictors of mortality included Glasgow Coma Score motor 2 to 5, systolic blood pressure greater than 90 mmHg, age, initial pulse rate in the emergency department, mechanism of injury, head Abbreviated Injury Score, and abdominal Abbreviated Injury Score. External benchmarking of trauma center performance using mortality prediction models is important in quality improvement for trauma patient care. From our results, TQIP methodology from the pilot study may not be applicable to all institutions.